URGENSI DAN RELEVANSI AL-MASLAHAH AL-MURSALAH SEBAGAI METODE IJTIHAD KONTEMPORER - Ach Cholili (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2013)
Justice of decision of law of problems that happened, have properly relied on theorem or nash of al-Qur’an, kitabullah which have been confessed its truth, as well as relying on rules of Rasulullah (as-Sunnah). Besides based on both theorem above, Islam also recognizestipulating of law by aqliyyah, which is [is] ordinary to be named with method of ijtihad birra’yi (with ratio), and one of the method named al-Mursalah al-Mashlahah, that is specifying an deed which not there are lasing base or its in and also al-Qur’an of Sunnah. In conception al-mursalah al-mashlahah told with different term. Some of moslem scholar use term of al-mashahah that al-mursalah with word of al-Munasib al-Mursal (Ibnu Hajib and of Baidhawi; al-Baidhawi al-Qadhi), there also using istihlah (al-Ghazali; al-mustasyfa) and some of other again mentioning of al-Istidlal al-Mursal (al-Syatibi; al-Muwafaqat). Difference of that name looked into from three facet. First, see mashlahah found on questioned case. Second, seeing the nature of matching with the target of syara’ (al-munasib al-washf) obliging the existence of something rule of law be created something maslahah. Third, see process stipulating of law to something mashlahah addressed by special theorem.